Optimizing Implant Macro-geometry to Improve Primary Stability in Low Bone Density: A Systematic Review - Fakhrana Ariani Ayub; Ratna Sari Dewi (Indonesian Dental Association, 2024)
Background: The design of the implant is a crucial factor that can impact the initial stability of the implant. Nevertheless, the current evidence is inadequate in establishing the most suitable dental implant design for cases with low bone quality to obtain the optimal amount of implant stability despite the availability of various options. Objective: The study aimed to perform a systematic review to assess the effect of different implant macro-geometry on primary stability in low bone density. Materials and Methods: The search strategy included both in vitro and in vivo studies published in PubMed, Cochrane Library, and Scopus from 2015 to 2024. The inclusion criteria were in vitro and in vivo studies, studies that evaluate implant primary stability by implant stability quotient (ISQ), insertion torque (IT), or removal torque (RT) value, studies that compare design thread in low bone density within the same study, and studies published in English. Results: 208 manuscripts were retrieved from the electronic literature search, and 11 studies met the eligibility criteria and were selected for this study. Conclusions: The results of this review suggested that an implant with a tapered body shape, square thread, and double-threaded feature significantly affects the primary stability of the implant in low bone density. It has become apparent that implant shape and thread geometry are critical parameters when designing new implant designs.